1,2,3,4,6-Penta-O-Galloyl-Beta-D-Glucopyranoside Inhibits Proliferation of Multiple Myeloma Cells Accompanied with Suppression of MYC Expression - Tseeleesuren, Duurenjargal; Kant, Rajni; Yen, Chia-Hung; Hsiao, Hui-Hua; Chen, Yi-Ming A. (Frontiers in Pharmacology, 2018)
Multiple myeloma (MM) still remains an incurable disease, therefore discovery of novel drugs boosts the therapeutics for MM. The natural compound 1,2,3,4,6-Penta-O-galloyl-beta-D-glucopyranoside (PGG) has been shown to exhibit antitumor activities against various cancer cells. Here, we aim to evaluate antitumor effects of PGG on MM cell lines. PGG inhibited the growth of three different MM cell lines in a dose- and time-dependent manner. Cell cycle analysis revealed that PGG treatment caused cell cycle arrest in G1 phase. It also induced apoptosis which was indicated by significant increases of Annexin V positive cells, caspase 3/7 activity, and cleaved caspase 3 expression in PGG treated MM cell. Since MYC is frequently hyperactivated in MM and inhibition of MYC leads to MM cell death. We further demonstrated that PGG decreased MYC expression in protein and mRNA levels and reversed the mRNA expression of MYC target genes such as p21, p27 and cyclin D2. In addition, PGG also reduced protein expression of DEPTOR which is commonly overexpressed in MM. Unexpectedly, PGG antagonized the cytotoxic effect of bortezomib in the combination treatment. However, PGG treatment sensitized MM cells to another proteasome inhibitor MG132 induced cytotoxicity. Moreover, MYC inhibitor JQ1 enhanced the cytotoxic effect of bortezomib on MM cells. Our findings raised concerns about the combinatory use of bortezomib with particular types of chemicals. The evidence also provide useful insights into the combination of MYC and proteasome-inhibitors for MM therapy. Finally, PGG has a therapeutic potential for treatment of MM and further development is mandatory.